Effect of Milk Fat Globule Size on the Physical Functionality of Dairy Products - Truong, Tuyen; Palmer, Martin; Bansal, Nidhi; Bhandari, Bhesh; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
Effect of Milk Fat Globule Size on the Physical Functionality of Dairy Products provides a comprehensive overview of techniques utilized to vary milk fat globule size in fat-structured dairy products. The text aims to highlight the importance of both native and emulsified milk fat globule size in the processing and functionality of these products. Both herd managements strategies and fractionation techniques utilized to vary milk fat globule size are covered thoroughly, as are the effects of mechanical sheer processing. The influence of different size fat globules on aspects such as TAG composition, physical stability, viscosity, crystallization properties and electric conductivity are studied, as are the influences on processability and function. This Brief aims to highlight the importance of milk fat as a determinant of the microstructural, rheological and sensorial properties of fat-containing dairy products such as milk, cream, yogurt, ice cream, cheese, butter and milk chocolate. Since milk fat globules have a widely varied size distribution, controlling their size is of major importance in processing. In comprehensively covering the various methods used to vary milk fat globule size, this text serves as an important resource for those involved in dairy product processing.
Keywords: Food science; Chemistry, Organic; Food Science; Organic Chemistry